The Effect Of Organizational Culture And Emotional Intelligence On Employee Engagement With Work-Life Balance As A Moderating Variable - Yudi Nur Supriadi; Mikhayanti Sihombing (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of organizational culture and emotional intelligence on employee engagement, with work-life balance as a moderating variable. The research method uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Data were obtained through questionnaires distributed to 361 employees in the manufacturing industry in Tangerang City and analyzed using the SmartPLS application. The results show that organizational culture has no significant effect on employee engagement, while emotional intelligence has a positive and significant effect. In addition, work-life balance has a direct positive effect on employee engagement. Moderation tests show that work-life balance weakens the effect of organizational culture on employee engagement, but strengthens the effect of emotional intelligence on employee engagement. This finding presents the novelty that work-life balance can play a more dominant role than organizational culture in increasing employee engagement. The practical implication of this study is the need for companies to emphasize the development of employee emotional intelligence and create adaptive work-life balance policies to strengthen employee engagement. Meanwhile, organizational culture needs to be re-evaluated to align with employee welfare needs. Thus, this research not only enriches theoretical studies on employee engagement but also makes a tangible contribution to human resource management strategies in companies.